2010
DOI: 10.1007/s00125-010-1667-2
|View full text |Cite
|
Sign up to set email alerts
|

Global microRNA expression profiles in insulin target tissues in a spontaneous rat model of type 2 diabetes

Abstract: Aims/hypothesisMicroRNAs regulate a broad range of biological mechanisms. To investigate the relationship between microRNA expression and type 2 diabetes, we compared global microRNA expression in insulin target tissues from three inbred rat strains that differ in diabetes susceptibility.MethodsUsing microarrays, we measured the expression of 283 microRNAs in adipose, liver and muscle tissue from hyperglycaemic (Goto–Kakizaki), intermediate glycaemic (Wistar Kyoto) and normoglycaemic (Brown Norway) rats (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
226
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(244 citation statements)
references
References 44 publications
17
226
0
1
Order By: Relevance
“…Huang et al (2009) showed at least a twofold decrease in miR-23a/b, miR-24, miR-126, miR-130a, miR-424, and miR-450 and at least a twofold increase in miR-307 and let-7f in the skeletal muscle of GK rats vs Wistar rats. Herrera et al (2010) found a significant decrease in miR-10b in the skeletal muscle of GK rats compared with Wistar Kyoto rats and Brown Norway rats. He et al (2007) found an increase in miR-29a/b/c in the skeletal muscle of GK rats compared with normal Wistar rats.…”
Section: Mirnas and Insulin Resistancementioning
confidence: 82%
See 1 more Smart Citation
“…Huang et al (2009) showed at least a twofold decrease in miR-23a/b, miR-24, miR-126, miR-130a, miR-424, and miR-450 and at least a twofold increase in miR-307 and let-7f in the skeletal muscle of GK rats vs Wistar rats. Herrera et al (2010) found a significant decrease in miR-10b in the skeletal muscle of GK rats compared with Wistar Kyoto rats and Brown Norway rats. He et al (2007) found an increase in miR-29a/b/c in the skeletal muscle of GK rats compared with normal Wistar rats.…”
Section: Mirnas and Insulin Resistancementioning
confidence: 82%
“…Insulin resistance indicates that the peripheral tissues fail to respond to the normal level of insulin, and manifests as an elevated glucose level with decreased insulin-mediated glucose uptake in the skeletal muscle and adipose tissue, and as an impaired suppression of glucose output in the liver (Peppa et al 2010). Herrera et al (2009Herrera et al ( , 2010 profiled a cluster of miRNAs in insulin target tissues in Goto-Kakizaki (GK) rats, a spontaneous rat model of T2D, and found upregulation of miR-222 and miR-27a in adipose tissue; upregulation of miR-125a, miR-195, and miR-103 in liver; and downregulation of miR-10b in muscle.…”
Section: Mirnas and Insulin Resistancementioning
confidence: 99%
“…Additionally, metabolic disorders such as diabetes are associated with changes in the expression levels of the miR-200 family at peripheral tissues. Indeed, miR-200a is decreased in the kidney of non-obese diabetic apoE KO mice (Wang et al 2011) and in the liver of spontaneous diabetic non-obese GK rats (Herrera et al 2010). Interestingly, miR-200a is increased in liver of obese diabetic ob/ob mice (Li et al 2009) as well as in liver and pancreatic islets of obese diabetes-resistant B6-ob mice (Zhao et al 2009).…”
Section: Figurementioning
confidence: 98%
“…miR-278 mediates energy balance by regulating insulin responsiveness in Drosophila, and miR-278 mutants are insulin resistant [18]. Aberrant expression of miRNAs has been observed in the insulin-target tissues of rat and mouse models of type 2 diabetes [19][20][21]. In adipocytes, miR-320 induces insulin resistance by inhibiting the insulin-phosphoinositide 3-kinase (PI3K) signalling pathway [22].…”
Section: Introductionmentioning
confidence: 99%